Dinamika Sosial Keluarga di Era Digital: Studi tentang Pola Komunikasi antara Orang Tua dan Remaja - Fadila Rahma Batubara; Jihan Marwa Alya; Ezra Azzahra Hasibuan; Berlianti Berlianti; Alya Shalsabila Lubis; Aurelia Serbina Sitepu (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The digital era has fundamentally changed the way families communicate and interact. This study aims to analyze the social dynamics of families in the context of communication patterns between parents and adolescents in the digital era. Using a qualitative approach with a literature study method, this study examines various academic literature published in the period 2018-2025 to understand changes in family communication patterns due to the penetration of digital technology. The results of the study indicate that digital technology has created a paradox in family communication, where easy access to information and communication can actually create a communication gap between generations. Traditional face-to-face communication patterns have been transformed into digital communication mediated by various social media platforms and instant messaging applications. This phenomenon has an impact on the quality of parent-child relationships, patterns of socialization of family values, and dynamics of generational conflict. This study identifies four main communication patterns in digital families: hybrid communication (digital-analog combination), disconnected communication (digital divide), reactive communication (response to technology), and adaptive communication (adjustment to the digital era). The implications of these findings indicate the need for a balanced family communication strategy between the use of digital technology and maintaining the intimacy of direct communication to maintain family social welfare.